Analysis of the Accelerated Implementation of the North Boulevard Paramount Petals Road and Canal Project Using CPM, PERT And Time Cost Trade Off Integration Methods - Ibnu Fadillah; Rifaldi Adi Saputra (Jurnal Teknik dan Science, 2025)
The North Boulevard Road and Canal Project in the South Petals area is a project that has been under construction since June 2024 and is the main route for the Paramount Petals neighborhood. This project has a work time agreement of 120 normal days. For this reason, it is very important for the project to be completed on time or faster and not experience delays. In this final project, an analysis of project acceleration is carried out using the Critical Path Method scheduling method to determine the activities that are on the critical path and the Program Evaluation and Review Technique to determine the probability that the project can be completed on time. Based on the analysis carried out, it was found that the CPM duration is 120 days with the probability that it can be completed in 120 days is 50.38%. Then the results of the acceleration analysis using the Time Cost Trade Off method show that the optimal project duration is 100 working days with a normal reduction of Rp. 76,604,480.00 in addition to 1 hour of overtime work.